POOR COMMUNICATION SKILLS MEANS HIGH RISK FOR AVIATION SAFETY (Gestão & Regionalidade, 2014)
This article analyses different types of communication in the aviation operational environment. This research has a qualitative approach underlined by a documentary analysis based on national aviation agencies' reports. Communication is a complex system consisted by verbal, non-verbal, written, spoken and automatic communication. Communication is a crucial factor to manage critical situations. According to the results, the lack of communication skills among individuals involved in air operations contribute for the bulk of accidents and incidents in aviation. Conclusions show that aviation activities require people high skilled in communication as such as technical proficiency. Conclusions also stress the emergency of implementing Communication Skills Training to aviation professionals, in order to develop abilities to detect threats and communicate clearly the need for support to manage risks. It is imperative to certify that all the actions required by the Safety Management System's philosophy have been implemented to develop safety behavior.